Development and validation of machine learning models to predict survival of patients with resected stage-III NSCLC - Jin, Long; Zhao, Qifan; Fu, Shenbo; Cao, Fei; Hou, Bin; Ma, Jia (Frontiers in Oncology, 2023)
Objective To compare the performance of three machine learning algorithms with the tumor, node, and metastasis (TNM) staging system in survival prediction and validate the individual adjuvant treatment recommendations plan based on the optimal model. Methods In this Study, we trained three machine learning madel and validated 3 machine learning survival models-deep learning neural network, random forest and cox proportional hazard model using the data of patients with stage-III NSCLC patients who received resection surgery from the National Cancer Institute Surveillance, Epidemiology, and End Results (SEER) database from 2012 to 2017,the performance of survival predication from all machine learning models were assessed using a concordance index (c-index) and the averaged c-index is utilized for cross-validation. The optimal model was externally validated in an independent cohort from Shaanxi Provincial People’s Hospital. Then we compare the performance of the optimal model and TNM staging system. Finally, we developed a Cloud-based recommendation system for adjuvant therapy to visualize survival curve of each treatment plan and deployed on the internet. Results A total of 4617 patients were included in this study. The deep learning network performed more stably and accurately in predicting stage-III NSCLC resected patients survival than the random survival forest and Cox proportional hazard model on the internal test dataset (C- index=0.834 vs. 0.678 vs. 0.640) and better than TNM staging system (C-index=0.820 vs. 0.650) in the external validation. The individual patient who follow the reference from recommendation system had superior survival compared to those who did not.The predicted 5-year-survival curve for each adjuvant treatment plan could be accessed in the recommender system via the broswer. Conclusion Deep learning model has several advantages over linear model and random forest model in prognostic predication and treatment recommendations. This novel analytical approach may provide accurate predication on individual survival and treatment recommendations for resected Stage-III NSCLC patients